Tribbles homologue 3 stimulates canonical TGF-β signalling to regulate fibroblast activation and tissue fibrosis. Issue 3 (20th January 2015) - Tomcik, Michal; Palumbo-Zerr, Katrin; Zerr, Pawel; Sumova, Barbora; Avouac, Jerome; Dees, Clara; Distler, Alfiya; Becvar, Radim; Distler, Oliver; Schett, Georg; Senolt, Ladislav; Distler, Jörg H W
Abstract : Objectives: Tribbles homologue 3 (TRB3) is a pseudokinase that modifies the activation of various intracellular signalling pathways to control fundamental processes extending from mitosis and cell activation to apoptosis and modulation of gene expression. Here, we aimed to analyse the role of TRB3 in fibroblast activation in systemic sclerosis (SSc). Methods: The expression of TRB3 was quantified by quantitative PCR, western blot and immunohistochemistry. The role of TRB3 was analysed in cultured fibroblasts and in experimental fibrosis using small interfering RNA (siRNA)-mediated knockdown and overexpression of TRB3. Results: TRB3 expression was increased in fibroblasts of patients with SSc and in murine models of SSc in a transforming growth factor-β (TGF-β)/Smad-dependent manner. Overexpression of TRB3 stimulated canonical TGF-β signalling and induced an activated phenotype in resting fibroblasts. In contrast, knockdown of TRB3 reduced the profibrotic effects of TGF-β and decreased the collagen synthesis. Moreover, siRNA-mediated knockdown of TRB3 exerted potent antifibrotic effects and ameliorated bleomycin as well as constitutively active TGF-β receptor I-induced fibrosis with reduced dermal thickening, decreased hydroxyproline content and impaired myofibroblast differentiation. Conclusions: The present study characterises TRB3 as a novel profibrotic mediator in SSc. TGF-β induces TRB3, which in turn activates canonical TGF-β/Smad signalling and stimulates the release of collagen, thereby inducing a positive feedback loop that may contribute to aberrant TGF-β signalling in SSc.